2009
DOI: 10.1016/j.otsr.2009.04.004
|View full text |Cite
|
Sign up to set email alerts
|

Distal femur rotational alignment and patellar subluxation: A CT scan in vivo assessment

Abstract: Prospective diagnostic study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
21
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(26 citation statements)
references
References 14 publications
2
21
0
Order By: Relevance
“…Yang et al [ 18 ] suggested that the dysplastic distal femoral condyle was composed of anterior and posterior femoral condylar dysplasia. In accordance with previous studies on CT images [ 17 , 20 , 22 ], the results of our study by MRI showed that patients with PD was in the presence of posterior femoral condylar dysplasia: longer medial and shorter lateral posterior condyle, and larger PCA. Previous studies focused on identifying a reference point that could avoid the influence of the femoral trochlea on assessing the lateralization of the tibial tubercle in patients with trochlear dysplasia, such as the TT-PCL distance and TT-RA distance [ 15 , 16 ], while ignoring the PCRL—the reference line in most measurements—may be affected by posterior femoral condylar morphology (the posterior condylar dysplasia could make the PCRL more internal rotation).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Yang et al [ 18 ] suggested that the dysplastic distal femoral condyle was composed of anterior and posterior femoral condylar dysplasia. In accordance with previous studies on CT images [ 17 , 20 , 22 ], the results of our study by MRI showed that patients with PD was in the presence of posterior femoral condylar dysplasia: longer medial and shorter lateral posterior condyle, and larger PCA. Previous studies focused on identifying a reference point that could avoid the influence of the femoral trochlea on assessing the lateralization of the tibial tubercle in patients with trochlear dysplasia, such as the TT-PCL distance and TT-RA distance [ 15 , 16 ], while ignoring the PCRL—the reference line in most measurements—may be affected by posterior femoral condylar morphology (the posterior condylar dysplasia could make the PCRL more internal rotation).…”
Section: Discussionsupporting
confidence: 93%
“…The transepicondylar axis has been proven to be a reliable and constant reference line on the distal femoral condyles [ 19 ], consisting of anatomical and surgical transepicondylar axis (AEA and SEA, respectively). Both of them have been poorly studied in patients with PD [ 17 , 20 , 21 , 22 , 23 ]. We first proposed to measure the TT-TG distance using AEA and SEA as reference lines on axial MRI slices (TT-TGa and TT-TGs, respectively), which were theoretically independent of posterior femoral condylar dysplasia.…”
Section: Introductionmentioning
confidence: 99%
“…Rotational malalignment of the femoral components can cause patellofemoral complications such as patellar subluxation and late patellar prosthesis failure [1,2,5,21]. Ligament balance abnormalities can lead to knee instability and lift-off in weight-bearing activities [16,29].…”
Section: Introductionmentioning
confidence: 99%
“…Maltracking may result from excessive or unbalanced tension in the surrounding soft tissues during knee flexion, so our radiographic measurements do not reflect patello-femoral congruence during ROM. A CT scan or MRI in vivo assessment might be necessary [18,40,41]. Anyway, Varadarajan et al [42] demonstrated that, even with a correct external rotation, the trochlear groove in current TKA designs only partially restores normal anatomy.…”
Section: Discussionmentioning
confidence: 99%